Bright Stranger : Poems - Soniat, Katherine (Book collections on Project MUSE., 2016)
In her beguiling new collection, Bright Stranger, Katherine Soniat invites the reader to celebrate the unfinished and unsure. The poems in this volume do not demand or offer certainty, existing instead in the spaces between the real and the imagined, between past and present and future. They explore the human connection to nature, contemplating loss in the erosion of rock spires and rebirth in the blossoming of an amaranth. Visually playful lines recall the poems' existence in the physical world, even as Soniat's words transport the reader from the rugged isolation of the Grand Canyon, to the elements within the periodic table, and on to "the unwinding spool of grey" in the mythic underworld of Hades. Bright Stranger offers a soaring vision of the world in all its chaos, bewilderment, and joy.